Multi attribute decision model for orchard renewal - case study in Bosnia and - Pažek, Karmen (Agricultura (Maribor), 2005)
The fruit production in Bosnia and Herzegovina (BIH) is slowly returning to normality after Balkan wars. Due to favorable climatic and soil conditions it presents a clear business opportunity for family farms. The decision which fruit species/variety to grow is a complex decision and should be made on the basis of sound empirical analysis. This paper present a multi criteria model for planning and decision making methodology based on expert system DEX-i. In the first stage the technological and financial cost benefit analysis were conducted for each fruit production alternative. The results were further evaluated with expert system DEX-i considering all possible criteria influencing the fruit grower decision. In the case of a sample family farm the plum yielded with best multi criteria evaluation, followed by apple and pear, while sour cherry gave unsatifactory outcome.
Keywords: sadjarstvo; planiranje; proizvodi; Bosna in Hercegovina; Bosnia and Herzegovina